Adaptasi Petani Bawang Merah di Desa Mekarmanik dalam Menghadapi Perubahan Iklim - Sugiharti, Eva Ratna; Setiawan, Iwan; Noor, Trisna Insan (Universitas Galuh, 2025)
Climate change significantly impacts the agricultural sector. Shallots, a high-value horticultural crop, are particularly vulnerable to these climatic shifts. This study aims to identify the adaptation strategies implemented by shallot farmers in anticipation of climate change. The research employs a qualitative approach with descriptive analysis. Informants were selected purposively, focusing on shallot farmers in Mekarmanik Village, Cimenyan District, who have cultivated shallots for at least a decade. Data collection techniques included observation, interviews, and literature review. The findings reveal that farmers have adopted adaptive strategies encompassing crop pattern adjustments, irrigation water management, and mulch application.